Snowbound mystery. - Warner, Gertrude Chandler, 1890-1979.; Cunningham, David, 1938- (Chicago, A. Whitman, 1968)
A family, snowbound in a vacation cabin, discovers adventure in surrounding wild life, three children they find in the snow, and a search for a lost recipe.
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Orphans -- Juvenile fiction; Families -- Juvenile fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Families -- Fiction; Mystery fiction